the Role and influence of corporate leader values on corporate governance mechanisms and financial reporting quality - Wan Abdullah, Wan Zalani @ Wan Zanani (2016)
Even after twenty years of implementing corporate governance system, corporate scandals and failures are still happening. Most empirical studies show inconsistent and at best, inconclusive findings regarding the effects of corporate governance mechanisms such as board and audit committee characteristics and ownership structure on a quality of financial reporting. The effectiveness of corporate governance is also affected by institutional factors that are shaped by history and political contexts. Most corporations in developing countries including Malaysia demonstrate high concentration ownership, government intervention and family dominance. This would lead to low transparency, inadequate disclosure and minority shareholder expropriation as majority shareholders tend to maximise their private benefits. The enforcement of corporate governance principles practised by corporations does not reflect the quality of corporate people who actually govern the corporations. Hence, it is important to study the role of corporate leader values as an organization is typically shaped up by the attitude, values and vision of a corporate leader. The vision, philosophy, future direction shared by the CEO is important to corporations in ensuring all governance related matters are handled as efficiently and as effectively as possible. The values held and shared by the leader will shape the extent of reporting quality by the corporation.